Immune Infiltration, Cancer Stemness, and Targeted Therapy in Gastrointestinal Stromal Tumor - Wang, Jingjing; Ren, Hui; Wu, Wenhui; Zeng, Qianlin; Chen, Jingyao; Han, Juanjuan; Lin, Minquan; Zhang, Changhua; He, Yulong; Li, Mingzhe (Frontiers in Immunology, 2021)
Objective: To investigate the characteristics of tumor immune microenvironment in patients with gastrointestinal stromal tumor (GIST), and identify GIST stemness molecular signature to screen potential target drugs. Methods: The gene expression data of 60 patients were from ArrayExpress database. CIBERSORT was used to calculate the infiltration degree of immune cells. The ssGSEA and ESTIMATE was used to calculate the cancer stemness index and tissue purity. CMAP database was used to predict the drugs targeting the GIST stemness signature. Result: There was a difference in the level of immune cell infiltration between metastasis and non-metastasis group. The low level of T cell infiltration was correlated with higher tumor purity and tumor stem index, and the correlation coefficients were - 0.87, - 0.61 (P < 0.001), respectively. The correlation analysis between cancer stemness index and cell purity showed a positive correlation. The correlation between cancer stemness index and cell purity was positive (P < 0.001). The cancer stemness index in the metastasis group was higher than that in the non-metastasis group (P = 0.0017). After adjusting for tumor purity, there was no significant correlation between T cell infiltration and cancer stemness index (P = 0.086). Through the pharmacological mechanism of topoisomerase inhibitors, six molecular complexes may be the targets of GIST treatment. Conclusion: GIST immune infiltration is related to cancer stemness and depends on tumor purity. Stemness molecular signature can be used as a new prediction biomarker of tumor metastasis and as a target for drug therapy.